Rancang Bangun Sistem Pendataan Mahasiswa Dan Rekap Nilai, Presensi Praktikum Stimik Sepuluh Nopember Jayapura Berbasis Web - Elton Fenetiruma; Jim Lahallo (Jurnal Informatika dan Komputer, 2023)
The laboratory is a tool and setting to support the implementation of learning as it relates to the growth of knowledge, abilities, and scientific discoveries. Various tasks performed in the lab, like practicum and administrative tasks in the computer training laboratory, are still done manually using a computer but are not based on information methods. The previous laboratory website is still used for data collecting for practicum participants and recaps of practicum vacations. As a result, they frequently run into problems while trying to recapitulate student data, track attendance for practicum activities, or even teach vacation recap. This is due to an outdated system still having issues. Taking into account the foregoing context, this essay will outline the steps involved in creating a laboratory information system that can